ANALISIS PENILAIAN WISATAWAN BENCANA TERHADAP CITRA PARIWISATA ACEH (SURVEY PADA WISATAWAN MUSEUM TSUNAMI TAHUN 2016) - Nuzura .; Alamsyah .; Yusya . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
The earthquake and tsunami that occurred in Aceh in 2004 became the highlights for the world community. Its cause many tourist to visit directly, how effect of disaster. Tsunami museum is icon of Aceh’s Tsunami became purpose for half of tourist to know about earthquake and tsunami that occured in 2004 ago. In this reasearch, analysis effect of visiting tourist to Aceh Tsunami Museum on their knowladge about earthquake and tsunami disaster, and also about Aceh image tourism, strategize and recommendation to develope Tsunami museum tourism, Aceh. This reasarch in descriptive which as population is tourist, who visiting to tsunami turism at Banda Aceh, an quantity of sample is 80. The result, that knowladge on earthquake and tsunami Aceh can improved by visiting Aceh Tsunami Museum. Its positive side for tourism, site of Aceh Tsunami Museum clearly and nearly, because it on the spot disaster, so level knowladge more accurate. Beside, majority of respondend has satisfied on visiting Aceh Tsunami Museum, so it can be said that aceh image tourism is good. Then, condition of Aceh more great and gracious to visiting also make them comfortable to travelling, and recommendation tourism to visit again for herself or others.Keywords : Tourist knowledge of disaster, Aceh Tourism Image, and Aceh Tsunami Museum